Reflections on the Afrogoth Hashtag on Tiktok: strategies for hacking the dispositive of raciality in digital media technologies - de Sobral Gomes, Amanda Maria (AoIR Selected Papers of Internet Research, 2026)
The paper analyzes the term afrogoth, or afrogotic, on TikTok, from afrocentric perspectives on digital technologies, with the aim of investigating the impact of the hashtag in subverting algorithmic racism and the low visibility that black goth people receive on social networks, as well as digital aquilombamento and the creation of self-definitions. The rationale addresses Goth subculture, Technological Pretuguese, algorithmic racism, hacking the dispositive of raciality and cyberquilombism. The methodology includes the collection of videos with #afrogoth. The results show mostly black bodies using elements constructed as feminine. The creation and use of the term afrogoth is a form of Technological Pretuguese, in which technology itself is used to go against white supremacy, creating a language that refers to blackness. In addition, it emerges as a self-definition, in which Black people can name themselves within Goth Subculture, valuing their blackness and seeking more equality in goth spaces, proposing cyberquilombism by forming a network of visibility and support among Black goth people.